Characterization and Prognostic Significance of Methylthioadenosine Phosphorylase Deficiency in Nasopharyngeal Carcinoma. Issue 49 (December 2015) - He, Hong-Lin; Lee, Ying-En; Shiue, Yow-Ling; Lee, Sung-Wei; Chen, Tzu-Ju; Li, Chien-Feng
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Identification of cancer-associated genes by genomic profiling contributes to the elucidation of tumor development and progression. The methylthioadenosine phosphorylase ( MTAP ) gene, located at chromosome 9p21, plays a critical role in tumorigenicity and disease progression in a wide variety of cancers. However, the prognostic impact of MTAP in patients with nasopharyngeal carcinoma (NPC) remains obscured. Through data mining from published transcriptomic database, MTAP was first identified as a differentially downregulated gene in NPC. In this study, our aim was to evaluate the expression of MTAP in NPC and to clarify its prognostic significance. MTAP immunohistochemistry was retrospectively performed and analyzed in biopsy specimens from 124 NPC patients who received standard treatment without distant metastasis at initial diagnosis. The immunoexpression status was correlated with the clinicopathological variables, disease-specific survival (DSS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS). Real-time quantitative polymerase chain reaction (PCR) was used to measure MTAP gene dosage. In some cases, we also performed methylation-specific PCR and pyrosequencing to assess the status of promoter methylation. MTAP deficiency was significantly associated with advanced tumor stages ( P  = 0.023) and univariately predictive of adverse outcomes for DSS, DMFS, and LRFS. In the multivariate comparison, MTAP deficiency still remained prognostically independent to portend worse DSS ( P  = 0.021, hazard ratio = 1.870) and DMFS ( P  = 0.009, hazard ratio = 2.154), together with advanced AJCC stages III to IV. Homozygous deletion or promoter methylation of MTAP gene were identified to be significantly associated with MTAP protein deficiency ( P  < 0.001). MTAP deficiency was correlated with an aggressive phenotype and independently predictive of worse DSS and DMFS, suggesting its role in disease progression and as an independent prognostic biomarker of NPC, which potentially offers new strategy of targeted treatment for patients lacking MTAP expression.